Social Change in the Digitalization Era of Indonesian Consumerism on E-Commerce Platforms - Zair, Ika Octavianie; Sy. Nurul Syobah; Inayah, Sitti Syahar (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has had a significant impact on various aspects of people's lives, especially in terms of consumption behavior. This research aims to understand how digitalization, particularly through social media and e-commerce platforms, affects people's consumptive patterns in the modern era. Using a descriptive qualitative approach, this research involves informants from various backgrounds who actively use digital technology in consumption activities. The results show that easy access to information, attractive visual promotions, and the influence of influencers significantly encourage consumptive behavior, especially in the form of impulse purchases. In addition, digital payment systems such as paylater also contribute to weak financial awareness. This research emphasizes the importance of digital and financial literacy in facing consumption challenges in the digital era. Educational efforts and strengthening critical awareness are needed so that people are able to adapt wisely to technology, and are able to balance consumption needs with personal economic stability. The findings are relevant for policy makers, digital industry players, and educational institutions in designing a comprehensive digital literacy improvement strategy.